The impact of socio-demographic features on anxiety and depression amongst navy veterans after retirement: a cross-sectional study - Georgantas, Dimitris; Tsounis, Andreas; Vidakis, Ioannis; Malliarou, Maria; Sarafis, Pavlos (My University, 2020)
Retirement from work may trigger various changes in everyday life that affect mental health. The current cross-sectional study, conducted with 231 veterans, examines the relationship between socio-demographic features and both anxiety and depression in navy veterans after retirement. Spielberg's State-Trait Anxiety Inventory (STAI) was used for anxiety assessment, and the Beck Depression Inventory (BDI) was used for depression assessment. The analysis was performed with the Statistical Package for Social Sciences (SPSS), version 20.0.
Keywords: Anxiety; Depression; Navy; Retirement; Veterans